1990
DOI: 10.1021/es00071a015
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of aminonaphthalene and quinoline on amorphous silica

Abstract: The adsorption of quinoline and aminonaphthalene was investigated from aqueous solution on amorphous silica @io2). Amorphous Si02 was not a strong adsorbent of these compounds and quinoline was adsorbed more strongly than aminonaphthalene. The adsorption of both compounds varied with pH. A maximum in adsorption occurred near their respective pK,'s. Temperature effects were significant, suggesting enthalpy contributions in the range of H bonding. Both compounds appeared to adsorb via identical mechanisms that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 32 publications
2
33
0
1
Order By: Relevance
“…For example, Zachara et al [17] found that the adsorption of aminonaphthalene and quinoline onto amorphous silica over the pH range from 3 to 8 decreased as temperature increased. This result is in accord with our study, since the silica surface will be negatively charged over this pH range.…”
Section: The Effect Of Temperature On Mellitic Acid Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Zachara et al [17] found that the adsorption of aminonaphthalene and quinoline onto amorphous silica over the pH range from 3 to 8 decreased as temperature increased. This result is in accord with our study, since the silica surface will be negatively charged over this pH range.…”
Section: The Effect Of Temperature On Mellitic Acid Adsorptionmentioning
confidence: 99%
“…This small enthalpy change is consistent with the notion that mellitate-substrate bonds are the result of electrostatic and hydrogen bonding interactions (outer-sphere complexation). Zachara et al [17] found that the adsorption of both quinoline and aminonaphthalene to amorphous silica were usually exothermic, but depended on the temperature interval and surface coverage. They also suggested that adsorption was non-specific because the enthalpies spanned the range usually associated with van der Waals and hydrogen bonding.…”
Section: Thermodynamic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorption into pores diminishes the efficacy of chemical extraction and reduces the bioavailability of such compounds [2,[5][6][7]. Studies of hydrophobic organic contaminants (HOCs) indicate that several physical and chemical mechanisms, including increased adsorption energy resulting from compound interaction within pores, may enhance HOC retention in mineral micropores with a porous adsorbents effectively remove organic compounds and heavy metals from contaminated waters [12][13][14][15][16][17][18][19]. Other evidence also supports the likelihood that mineral mesopores may enhance organic compound sorption processes.…”
Section: Introductionmentioning
confidence: 99%
“…The models of surface complex formation were successfully applied to describe the adsorption of metal ions, inorganic anions, and organic substances on the surface of oxide minerals [8][9][10].…”
Section: Resultsmentioning
confidence: 99%